1973
DOI: 10.1007/bf01405405
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular space and electrolyte distribution in cortex and white matter of dog brain in cold induced oedema

Abstract: Summary24 hours after a circumscribed cold injury of the cortex dog brains were perfused from the lateral ventricle and the frontal subaraehnoidal space to the eisterna magna with an artificial CSF containing trace amounts of 35S-labelled thiosulphate. Simultaneously the extraeellular tracer was administered intravenously.Extracellular fluid volume was estimated and found to be increased from 10 to 15% in the oedematous cortex and from 10 to 27% in the oedematous white matter. The actual size of ECS in oedemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Interestingly, we found that cortical grey matter and subcortical white matter exhibit greatly different propensities for tissue swelling after cerebral ischemia. After ischemia, the ipsilateral cortical grey matter was swollen by 8.95 % ± 2.64 % compared to the contralateral cortex, while the ipsilateral subcortical white matter was swollen by a remarkable 42.5 % ± 8.84 %.These findings are in alignment with data from prior studies showing that white matter is highly susceptible to swelling after acute CNS injury [ 25 , 26 ]. There are at least two possible mechanistic explanations for the striking swelling exhibited by subcortical white matter: firstly, for reasons yet to be clarified, subcortical white matter may be more susceptible to the formation of edema fluid than cortical grey matter; secondly, subcortical white matter might be simply serving as a sink for edema fluid generated elsewhere [ 70 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, we found that cortical grey matter and subcortical white matter exhibit greatly different propensities for tissue swelling after cerebral ischemia. After ischemia, the ipsilateral cortical grey matter was swollen by 8.95 % ± 2.64 % compared to the contralateral cortex, while the ipsilateral subcortical white matter was swollen by a remarkable 42.5 % ± 8.84 %.These findings are in alignment with data from prior studies showing that white matter is highly susceptible to swelling after acute CNS injury [ 25 , 26 ]. There are at least two possible mechanistic explanations for the striking swelling exhibited by subcortical white matter: firstly, for reasons yet to be clarified, subcortical white matter may be more susceptible to the formation of edema fluid than cortical grey matter; secondly, subcortical white matter might be simply serving as a sink for edema fluid generated elsewhere [ 70 ].…”
Section: Discussionsupporting
confidence: 89%
“…Given that the human prefrontal cerebrum is ~2/5ths white matter [ 23 ], white matter integrity after stroke is a stronger functional predictor than preserved neurological function [ 24 ]. Insofar as certain studies indicate that white matter is highly susceptible to swelling after acute CNS injury [ 25 , 26 ], it is important to determine whether astrocyte regional heterogeneity manifests as significant differences in certain molecular events that drive cerebral edema formation.…”
Section: Introductionmentioning
confidence: 99%
“…White matter hyperintensities (WMH) [2] and abnormalities in fluid homeostasis in the white matter are frequent radiological observations in neurodegenerative diseases. White matter is highly susceptible to oedema after acute injury to the central nervous system (CNS) [27][28][29] and WMH are a common finding on computer tomography (CT) or magnetic resonance imaging (MRI) in the elderly, in stroke, dementia and cerebral amyloid angiopathy (CAA) [30]. Dilated perivascular spaces visible on MRI have been described in the white matter of patients with Alzheimer's disease (AD) or CAA [31].…”
Section: Introductionmentioning
confidence: 99%
“…,2~ In vasogenic brain edema associated with brain injury, tumor, or inflammation, the ECS is significantly enlarged) , 9,19,21 These dilated spaces may provide a pathway for the movement of edema fuid. The two mechanisms by which the edema fluid and its constituents might spread through these spaces are diffusion and bulk flow) 6,27 These two possible processes may be identified by their distinctive properties.…”
mentioning
confidence: 99%